Physicochemical properties for Toyyib environmental assessment on lake water quality: a mini review - Wan Sulaiman, Wan Syibrah Hanisah; Othman, Rashidi; Mohd Latiff, Nur Hanie; Ramya, Razanah; Mohd Hatta, Farah Ayuni (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia, 2023)
As Malaysia strives to become industrialised, numerous water bodies are increasingly dumping grounds for chemicals, sewage, and pollutants. It is considered that pollutant substances are continuously channelled into water bodies and then transferred into organic and inorganic particles, nutrients, pesticides, and herbicides that directly affect the aquatic ecosystem. This paper aims to study the overview of physicochemicals properties for lake water quality in relation to Toyyib environmental assessment. Malaysian water quality assessments are based on several rules, including the National Lake Water Quality Criteria and Standard, Urban Storm Water Management Manual for Malaysia, and National Water Quality Index Standard. As a result of the transmission of physicochemical qualities, water contaminants inflict harm not only on aquatic ecosystems but also on the safe water for human use. These studies indicate the water quality measurements or parameters for assessing the water quality for the Toyyib environment and establish the list of physicochemical properties for water quality assessment on the lake. On the other hand, the methodology applied for each parameter was also studied and presented.